2014
DOI: 10.1177/0192512114541163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of online data availability: The case of economic and institutional transparency in sixteen Latin American nations

Abstract: We adopt the principal-agent framework and the asymmetry of information between the principal and the agent in order to approach two subjects of much attention and expectations: i) the formal online release of governmental data as a means of furnishing information, and ii) its contribution to government economic and institutional transparency. We identify important characteristics of transparency as instruments to lessen the information asymmetry in relevant areas (or subjects) where corruption and inefficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
1
35
0
5
Order By: Relevance
“…858–59). There are also deeper questions about whether technological ‘sophistication’ alone is sufficient to drive change (Murillo , p. 42).…”
Section: Open Data In the Ukmentioning
confidence: 99%
See 1 more Smart Citation
“…858–59). There are also deeper questions about whether technological ‘sophistication’ alone is sufficient to drive change (Murillo , p. 42).…”
Section: Open Data In the Ukmentioning
confidence: 99%
“…This was seen in the USA where the first incarnation of the http://data.gov site was undermined by a negative spiral of ambiguous goals, political infighting, and minimal compliance (Peled ). A recent study across 16 Latin American countries concluded that new data portals were not ‘meeting expectations’ regarding anti‐corruption (Murillo , p. 42). Access to information legislation is perhaps a precursor here, as a radical information reform policy later subject to pushback and incremental weakening due to overly‐ambitious aims and the second thoughts of politicians (Worthy ).…”
Section: The Use and Impact Of Open Datamentioning
confidence: 99%
“…ICT tools created to collect feedback directly from citizens can change accountability relationships, such that new channels between development aid recipients and the institutions serving them have been created [12]. Governments making public data available for free, hope to deliver greater transparency and accountability towards citizens [13,14]. However, the links between accountability and open development are far more pervasive.…”
Section: Introductionmentioning
confidence: 99%
“…Transparency is considered the precursor of accountability (GARCIA and SORIANO MALDONADO, 2012; AL-JAMAL and ABU-SHANAB, 2016) and is closely connected to a reduction in levels of corruption, through the accountability of public officials (MURILLO, 2015), even though the relationship between them is not complete (WORTHY, 2015). However, the lack of data quality is a risk to transparency (KOUSSOURIS et al, 2015), as well as the lack of policies that ensure the continued availability of updated data (NUGROHO et al, 2015;SOLAR et al, 2014;LEONTIEVA et al, 2015).…”
Section: Figure 3 -Dimensions and Number Of Studiesmentioning
confidence: 99%